Perlindungan Hukum Konsumen bagi Penarikan Paksa Kendaraan oleh Debt Collector - Novia Dwi Khariati (Faculty of Law Hang Tuah University, 2020)
The pandemic currently being experienced by Indonesia and even throughout the world, namely Covid-19, has resulted in an increase in the needs that exist in society. One of them is the need to make ends meet. Many people today make loans to financial institutions. Basically, in carrying out a contract or agreement, there are consumers who must be protected, in accordance with Law Number 8 of 1999. Every consumer must have their rights protected and guarantees regarding consumer protection get enough attention because as consumers they should be protected from various fraudulent transactions given the right to get clear information and of course the right not to discriminate. Contracts originate from differences or differences in interests between the parties, both parties must show an active attitude in order to reach an agreement so that the intended profit can be obtained. The consequences that arise from this condition of default cause an agreement to be canceled and which is null and void. The formulation of the problem in this paper is how legal protection and dispute resolution for consumers against forced vehicle withdrawals by the deb collector. The purpose of this research is to find out how legal protection and dispute resolution can be carried out by consumers in protecting consumers from finance company companies that use debt collector services. This journal research uses normative juridical research methods, by examining legal norms in the legislation, legal theories and jurisprudence related to the issues discussed. This research approach uses a statutory approach (statute approach) and a conceptual approach (conceptual approach). Based on the results of the study, the authors obtained answers to the existing problems, namely, that the forced taking of a motorized vehicle in the financing agreement is that the consumer has committed default, but if the motor vehicle as an object of fiduciary security is not registered by the finance company at the Fiduciary Registration Office, then the forced retrieval is invalid. Then against forced taking that is not in accordance with these applicable provisions, consumers can file objections to the financing company based on mutual agreement in the financing agreement, but if it cannot be resolved, the consumer can report the forced taking based on the article of confiscation as regulated in the Book of Law Criminal Law (KUHP).